(4*x)-6=(x*2)+4

Simple and best practice solution for (4*x)-6=(x*2)+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4*x)-6=(x*2)+4 equation:


Simplifying
(4x) + -6 = (x * 2) + 4

Reorder the terms:
-6 + (4x) = (x * 2) + 4

Reorder the terms for easier multiplication:
-6 + (4x) = (2x) + 4

Reorder the terms:
-6 + (4x) = 4 + (2x)

Solving
-6 + (4x) = 4 + (2x)

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '(-2x)' to each side of the equation.
-6 + (4x) + (-2x) = 4 + (2x) + (-2x)

Combine like terms: (4x) + (-2x) = 2x
-6 + 2x = 4 + (2x) + (-2x)

Combine like terms: (2x) + (-2x) = 0
-6 + 2x = 4 + 0
-6 + 2x = 4

Add '6' to each side of the equation.
-6 + 6 + 2x = 4 + 6

Combine like terms: -6 + 6 = 0
0 + 2x = 4 + 6
2x = 4 + 6

Combine like terms: 4 + 6 = 10
2x = 10

Divide each side by '2'.
x = 5

Simplifying
x = 5

See similar equations:

| 5m+7m=-4m | | 5(4n-3)= | | x+6=x*4 | | 6.2x-3+4x-1.2= | | y=-2(-1-1)(-1+3) | | 7(x-4)= | | 2x-y=16 | | 3x+7-2x= | | 3(a+2)-8=5-2(a-4) | | X=24+4x | | 8+2z=24 | | 5x-10=3x-2 | | 10-6y=4y+9 | | 6Y-32+4Y-11=Y-12+4 | | 60=20t+5t^2 | | -4(x-6)=28 | | 38x+45(100-x)=41*100 | | X-5x+4(x-8)=3x-8 | | 6w=x^2+8 | | 6+(x)=(x*4) | | 3c+5= | | 3x^2-35x-4=0 | | x+(x*12.36/100)=44 | | 57x-95=0 | | 6x+40=x^2 | | 1.3-6.9=5.97 | | 57x-95y=0slope | | x^6+(3+i)x^3+3i=0 | | 3+(5*x)=18+(x*2) | | h(x)=3-12x-12x^2 | | 2(x-1)-(x-1)=0 | | 7m-6=6m+0 |

Equations solver categories